Fiscal and monetary management for mitigating the harmful impacts of the global pandemic in Peru - Gomero Gonzales, Nicko Alberto (2021)
Objective: Determine how the monetary and fiscal measures implemented under a global health crisis scenario mitigated the negative effects on the national economy. Method: Descriptive, correlational, cross-sectional, and non-experimental research. Other information, obtained from official government sources, was used to perform statistical measurements. Results: A negative Pearson correlation was found between the issuance of money and the interest rate r = -0.46, which explains the fall in interest rates due to increases in working capital. The same type of relationship was found between the interest rate and business loans, with the coefficient r = -0.12, which shows the advance of loans due to the fall in the cost of money that generated favorable results in gross national product (GNP). Public spending contributed with a weak boost to this macroeconomic indicator, a fact that can be seen in the correlation of 0.014. Conclusion: The monetary and fiscal measures, materialized in the increase in working capital, the revitalization of loans, a decrease in interest rates and an increase in public spending, prevented a further deepening of the economic crisis, generating a slight but sustained recovery of GNP and employment, but always maintaining macroeconomic stability.